행정정보 데이터세트 기록관리 환경개선 모델 연구: 의료영상저장전송시스템(PACS)의 데이터세트를 중심으로 - 이선경; Lee, Sun-kyung (Journal of Records Management & Archives Society of Korea, 2022)
Currently, an implementation plan of administrative information dataset record management has been prepared; however, analyzing the specificity of various administrative information systems and preparing a reasonable level of management reference table by applying about 1.3% (EA portal registration system: 16,199, consulting system: 214) has its limitations. This study started by recognizing the importance of the records management environment in administrative information datasets. Based on the described information, the current records management environment was analyzed by dividing the six areas of the management reference table of the picture archiving and communication system (PACS) into three groups. Thus, a systematic environmental improvement model was proposed, enhancing the effectiveness of dataset records management in the field. Although there is a limitation in analyzing one of the dataset records management environments of various institutions, it is intended to help broaden the horizons of records management research. 현재 행정정보 데이터세트 기록관리 실행방안은 마련되었으나 약 1.3%(EA 포털 등록 시스템: 16,199개, 컨설팅 시스템: 214개)의 사례를 적용하여 다양한 행정정보시스템에 대한 특수성을 분석하고 합리적 수준의 관리기준표를 작성하기에는 한계가 있다. 본 연구는 행정정보 데이터세트에 있어 기록관리 환경의 중요성을 인식하는 것에서 출발하였다. 의료영상저장전송시스템(PACS)의 관리기준표 6개 영역을 세 개의 그룹으로 나누고 기술(description)된 정보를 기초로 현재의 기록관리 환경을 분석하였다. 그 결과 현장에서 데이터세트 기록관리의 효과를 높이기 위한 체계적인 환경개선 모델을 제안하였다. 다양한 기관의 데이터세트 기록관리 환경 중 하나의 사례 분석이라는 한계는 있으나 기록관리 연구의 지평을 넓히는데 도움이 되고자 한다.